Records of the Assistant Commissioner for the State of Texas, Bureau of Refugees, Freedmen, and Abandoned Lands, 1865-1869 - Henrich, Joseph; Gruber, Robert (National Archives, National Archives and Record Service, General Services Administration, 1973)
"The records consist of 10 volumes and some unbound documents. The volumes include letters received and a 'record of criminal offenses.' The unbound documents consist of letters and reports received. These records are part of the Records of the Bureau of Refugees, Freedmen, and Abandoned Lands, Record Group 105"--Introduction.